Bringing social relations back in: (re) conceptualising the 'Bullwhip Effect' in global commodity chains. (18th November 2008) - Selwyn, Ben
Contemporary economic globalisation is characterised by the global dispersal of production and sourcing, the spread of new 'lean' management techniques and the speeding up and expanding scale of international forms of interaction. These processes are regularly described and analysed in techno-managerial terms, especially within much global supply chain and global commodity chain literature. As a consequence, there is often an (implicit or explicit) assumption of a zero-sum relationship between capital mobility and labour's bargaining power. Within supply chain literature, the concept of the 'Bullwhip Effect' (BWE) refers to a situation where a small disruption in one part of the chain is magnified elsewhere in the chain. This article argues that the concept of the BWE can be re-conceptualised as a valuable took with which to investigate claims of labour's weakness, and that it can also help 'bring social relations back in' to much globalisation analysis.